2018
DOI: 10.1111/clr.13256
|View full text |Cite
|
Sign up to set email alerts
|

Regenerative surgical therapy for peri‐implantitis using deproteinized bovine bone mineral with 10% collagen, enamel matrix derivative and Doxycycline—A prospective 3‐year cohort study

Abstract: Regenerative treatment of peri-implantitis using a combined mixture of DBBMC, EMD and Doxycycline achieved promising results. The benefits of this protocol incorporating EMD should be tested in randomized clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
98
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(100 citation statements)
references
References 41 publications
2
98
0
Order By: Relevance
“…Across the 18 studies, disease recurrence was not commonly discussed or defined. Recession of the peri‐implant mucosa following treatment was documented in two studies, (Heitz‐Mayfield et al., ; Mercado, Hamlet & Ivanovski, ) which might impact on aesthetics, phonetics and comfort. However, patient‐reported outcome measures (PROMs) such as aesthetic outcomes; quality of life; and patient satisfaction; as well as cost satisfaction analyses were not reported in the included studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Across the 18 studies, disease recurrence was not commonly discussed or defined. Recession of the peri‐implant mucosa following treatment was documented in two studies, (Heitz‐Mayfield et al., ; Mercado, Hamlet & Ivanovski, ) which might impact on aesthetics, phonetics and comfort. However, patient‐reported outcome measures (PROMs) such as aesthetic outcomes; quality of life; and patient satisfaction; as well as cost satisfaction analyses were not reported in the included studies.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies in the systematic review incorporated a soft tissue graft as part of the treatment procedure (Bach, Neckel, Mall & Krekeler, ; Froum et al., , ; Mercado et al., ) or during supportive care (Roccuzzo et al., ). It has been suggested that the absence of an adequate band of keratinized peri‐implant mucosa may negatively influence treatment outcomes due to discomfort when performing oral hygiene resulting in increased plaque accumulation (Roccuzzo, Grasso & Dalmasso, ).…”
Section: Discussionmentioning
confidence: 99%
“…Most treatment strategies depend on the clinical situation considering probing depth, suppuration, periodontal indices such as bleeding on probing and plaque index as well as radiographic bone loss [3,[23][24][25] as decisive factors. Treatment may then range from implant debridement, resective and reconstructive surgery [23] to implant removal [26].…”
Section: Introductionmentioning
confidence: 99%
“…Most treatment strategies depend on the clinical situation considering probing depth, suppuration, periodontal indices such as bleeding on probing and plaque index as well as radiographic bone loss [3,[23][24][25] as decisive factors. Treatment may then range from implant debridement, resective and reconstructive surgery [23] to implant removal [26]. According to several authors, treatment of periimplantitis is considered as having an unpredictable outcome [6,20] in particular when evaluating the effectiveness of regenerative treatment [23,27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation